Abbot ʿĔnbāqom and Islam : the historical-theological significance of Anqäs’ä Amin’s contribution to Christian-Muslim engagement in sixteenth century Ethiopia - Bekele, Yohannes (Stellenbosch : Stellenbosch University, 2022)
Thesis (PhD)--Stellenbosch University, 2022.